2009
DOI: 10.1128/jvi.02565-08
|View full text |Cite
|
Sign up to set email alerts
|

Different Evolutionary Trajectories of European Avian-Like and Classical Swine H1N1 Influenza A Viruses

Abstract: In 1979, a lineage of avian-like H1N1 influenza A viruses emerged in European swine populations independently from the classical swine H1N1 virus lineage that had circulated in pigs since the Spanish influenza pandemic of 1918. To determine whether these two distinct lineages of swine-adapted A/H1N1 viruses evolved from avian-like A/H1N1 ancestors in similar ways, as might be expected given their common host species and origin, we compared patterns of nucleotide and amino acid change in whole genome sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 65 publications
7
114
0
Order By: Relevance
“…150 days) lowers the chance of re-infection. However, several studies have concluded that the EA lineage HA gene undergoes more antigenic drift than the CS lineage HA gene [8,24,35], and it has been hypothesized that this provided EA viruses with a selective advantage, contributing to it replacing CS and TR strains in Asia [8]. Antibodies arising from CS and TR infection cross-react with many (but not all) EA viruses, which could explain some adaptation observed in the EA lineage HA and NA genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…150 days) lowers the chance of re-infection. However, several studies have concluded that the EA lineage HA gene undergoes more antigenic drift than the CS lineage HA gene [8,24,35], and it has been hypothesized that this provided EA viruses with a selective advantage, contributing to it replacing CS and TR strains in Asia [8]. Antibodies arising from CS and TR infection cross-react with many (but not all) EA viruses, which could explain some adaptation observed in the EA lineage HA and NA genes.…”
Section: Discussionmentioning
confidence: 99%
“…Genes of the EA, CS and TR swine influenza lineages provide a unique system in which these questions can be studied as they originated in birds but have been established in pigs for different durations. In perhaps the only direct comparison of the molecular evolution of the CS and EA lineages, Dunham et al [24] found that the nucleotide base composition of both changed through time since their respective cross-species transmissions, although with no apparent difference in nucleotide substitution rate. However, this study was constrained by a small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, the situation is even more complex as, in addition to the above viruses, Eurasian avian-like H1N1 SIVs are present (1,6,7,10).…”
Section: Discussionmentioning
confidence: 99%
“…Independently, a novel lineage of avian-like H1N1 swine IAV emerged in Europe in 1979 that essentially replaced classical swine IAV [27,29,30]. This second lineage of swine IAV is enzootic throughout swine-producing regions of Western Europe, where it cocirculates with swine IAVs of the H3N2 and H1N2 subtypes [31,32]. All eight gene segments of the prototype H1N1 viruses of this lineage are thought to be derived from closely related Eurasian avian IAVs by a stable host switch without re-assortment, and this lineage is phylogenetically and antigenically distinct from the classical swine H1N1 lineage [29,[33][34][35].…”
Section: Current Global Situationmentioning
confidence: 99%